2009
DOI: 10.1021/je801009z
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of l-Proline in Subcritical HFC-134a and Supercritical CO2 Fluids

Abstract: A static method coupled with gravimetric analysis was used to measure the solubility of l-proline in subcritical 1,1,1,2-tetrafluoroethane (HFC-134a) and supercritical CO2 (scCO2). The solubility of l-proline is much higher in HFC-134a fluid than in scCO2. The solubilities of l-proline in HFC-134a and scCO2 are affected by temperature and pressure. The solubilities increase with increasing temperature and pressure for both scCO2 and HFC-134a solvents. The densities of scCO2 and subcritical HFC-134a were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…The calibration of capillary pycnometer was made through measuring the density of a NaCl solution at w = 0.10 from 303.45 to 353.15 K with a step of 10 K. The AARD between the measured values and the literature data was 0.21%. 29 Viscosities were measured by using Ubbelohde capillary viscometers with different fine capillaries (0.46, 0.58, 0.73, and 0.91 mm) and viscosity constants. The detailed measurement schematic and procedure were reported in our previous research.…”
Section: Methodsmentioning
confidence: 99%
“…The calibration of capillary pycnometer was made through measuring the density of a NaCl solution at w = 0.10 from 303.45 to 353.15 K with a step of 10 K. The AARD between the measured values and the literature data was 0.21%. 29 Viscosities were measured by using Ubbelohde capillary viscometers with different fine capillaries (0.46, 0.58, 0.73, and 0.91 mm) and viscosity constants. The detailed measurement schematic and procedure were reported in our previous research.…”
Section: Methodsmentioning
confidence: 99%
“…The main reason is that the volume of equilibrium cell for system R134a + PVA in this work is as small as 10 mL, which is more appropriate for the static method; while that for system CO 2 + PVA is 150 mL and more suitable for the dynamic method. Furthermore, it is found that most of the solubility measurements for solutes in SCCO 2 have been carried out using the dynamic method [37][38][39][40]; while the static method has been widely used in systems containing sub-R134a [18,19,41]. Both methods are reliable when applying the right experimental procedure.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…Then there comes the question that whether and what degree the dissolving capacity of subcritical R134a (sub-R134a) is higher than that of SCCO 2 . However, the comparison of dissolving capacity between sub-R134a and SCCO 2 is rarely reported in the published literature [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The static method, which had been adopted by our and other groups, was used to measure the solubility of polystyrene in sub‐R134a. A schematic diagram of the solubility measurement apparatus is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%